2015
DOI: 10.17795/ijcp-3856
|View full text |Cite
|
Sign up to set email alerts
|

Individually and Combined Water-Based Exercise With Ginger Supplement, on Systemic Inflammation and Metabolic Syndrome Indices, Among the Obese Women With Breast Neoplasms

Abstract: Background:Breast neoplasms has known as the most common cancer among the women worldwide, and relationship between obesity, metabolic syndrome, inflammation and cancer has been recognized since many years ago.Objectives:The aim of this study was to determine the individual and concomitant effect of 6-weeks water-based exercise and oral ginger supplement on markers that have related to metabolic syndrome and systemic inflammation in obese women with breast neoplasms.Patients and Methods:Forty women whose have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 21 publications
(31 reference statements)
0
27
0
Order By: Relevance
“…A total of 289 records were identified for the initial search, and 12 articles met the inclusion criteria, which were included in systematic review [ 21 – 32 ]. Since there were no results of outcomes of interest in two records [ 22 , 30 ], 10 articles were finally included in meta-analysis [ 21 , 23 29 , 31 , 32 ]. The details of the selection process and the reasons for exclusion of studies are summarized in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 289 records were identified for the initial search, and 12 articles met the inclusion criteria, which were included in systematic review [ 21 – 32 ]. Since there were no results of outcomes of interest in two records [ 22 , 30 ], 10 articles were finally included in meta-analysis [ 21 , 23 29 , 31 , 32 ]. The details of the selection process and the reasons for exclusion of studies are summarized in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, ginger supplementation has been found to notably reduce fasting blood sugar, HbA1c, and insulin resistance [85][86][87]. Additionally, lipid profiles (e.g., total cholesterol, and LDL-C), C-reactive protein, obesity-related cardiovascular risk factors have been found to reduce with ginger intake [24,[88][89][90]. In general, ginger has been found to indicate a beneficial effect on high dosage and long-term treatment in metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effect of ginger supplementation on CRP, Naderi et al have reported that the concentration of inflammatory markers including CRP was reduced in the group treated with ginger compared with the group receiving placebo (5); moreover, Karimi et al reported that the ginger supplementation caused a reduction of hs-CRP, IL-10, blood glucose, LDL, and TG, and an increase in HDL (14). Imani et al indicated that daily administration of 1,000 mg ginger reduces serum fasting glucose (15).…”
mentioning
confidence: 99%